2023
DOI: 10.3389/fimmu.2023.1185278
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection risk is higher in vaccinated patients with inflammatory autoimmune diseases or liver transplantation treated with mycophenolate due to an impaired antiviral immune response: results of the extended follow up of the RIVALSA prospective cohort

Manuela Rizzi,
Stelvio Tonello,
Cristiana Brinno
et al.

Abstract: BackgroundA relevant proportion of immunocompromised patients did not reach a detectable seroconversion after a full primary vaccination cycle against SARS-CoV-2. The effect of different immunosuppressants and the potential risks for SARS-CoV-2 infection in these subjects is largely unknown.MethodsPatients from the Rivalsa prospective, observational cohort study with planned anti SARS-CoV-2 third dose mRNA vaccination between October and December 2021 were asked to participate to this follow-up study. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…An increasing number of case reports and research pieces suggest a possible heightened risk of LE development in association with COVID-19 infection and vaccination. Through a univariate analysis model study, Zecca et al revealed that there was no correlation between SLE and vaccination failure (27) ; Rizzi et al through univariate analysis showed that SLE was not associated with COVID-19 infection after the third dose of vaccine (28). Nevertheless, current broad-scale studies fall short of providing exhaustive clinical outcome data for COVID-19 patients simultaneously afflicted with CLE.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of case reports and research pieces suggest a possible heightened risk of LE development in association with COVID-19 infection and vaccination. Through a univariate analysis model study, Zecca et al revealed that there was no correlation between SLE and vaccination failure (27) ; Rizzi et al through univariate analysis showed that SLE was not associated with COVID-19 infection after the third dose of vaccine (28). Nevertheless, current broad-scale studies fall short of providing exhaustive clinical outcome data for COVID-19 patients simultaneously afflicted with CLE.…”
Section: Discussionmentioning
confidence: 99%